2020
DOI: 10.21203/rs.3.rs-56822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multidimensional Analysis of the Learning Curve of Laparoscopic Colorectal Surgery in a Regional Hospital. The Implementation of a Standardised Surgical Procedure Counterbalances the Lack of Experience.

Abstract: Background: Although in the last few years a larger proportion of colorectal surgeries have been performed laparoscopically, a steep learning curve prevents us from considering laparoscopic colorectal surgery as the gold standard technique for treating disease entities in the colon and rectum. The purpose of this single center study is to determine, using various parameters and following a well structured and standardised surgical procedure, the adequate number of cases after which a single surgeon qualified i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this study, a reduction in operative times was observed for both the specialized and non-specialized surgeons, being proportional to the number of operations performed by each of them. The operative time decreases with the surgeon's increasing experience, and it is a useful criterion for evaluating the learning curve [24]. At the same time, the specialized surgeon proved to have a greater reduction in operative times compared to the non-specialized surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a reduction in operative times was observed for both the specialized and non-specialized surgeons, being proportional to the number of operations performed by each of them. The operative time decreases with the surgeon's increasing experience, and it is a useful criterion for evaluating the learning curve [24]. At the same time, the specialized surgeon proved to have a greater reduction in operative times compared to the non-specialized surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the specialized surgeon proved to have a greater reduction in operative times compared to the non-specialized surgeons. It has been previously showed that the surgeon's expertise is reversible proportional to the operative time indicating the point where the learning curve is completed by reaching a steady level of performance [24,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation